2009
DOI: 10.1007/s12126-009-9044-5
|View full text |Cite
|
Sign up to set email alerts
|

Older Persons: the Case of South Africa

Abstract: The South African Constitution (Act 108 of 1996) laid the foundation for the transformation agenda of the new democracy to protect the human rights of older persons and to terminate all the forms of racial discrimination and inequality that had been instituted against them by the apartheid state. New legislation was passed in 2006, making provision for the protection of the rights of older persons and shifting services from primarily institutional care to community-based care, with a view to keeping the elderl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 13 publications
0
41
0
Order By: Relevance
“…These inequities led to limited access to education and unemployment, with resultant poverty, especially for black South Africans. 19 The possible effects of previous racial inequities were made clear in the current study. The results established that elderly residents fetch their own drinks and visit the restroom frequently.…”
Section: Discussionmentioning
confidence: 70%
“…These inequities led to limited access to education and unemployment, with resultant poverty, especially for black South Africans. 19 The possible effects of previous racial inequities were made clear in the current study. The results established that elderly residents fetch their own drinks and visit the restroom frequently.…”
Section: Discussionmentioning
confidence: 70%
“…The review revealed that the high incidence of HIV/AIDS in SSA has resulted in devastation and disruption of the traditional family structure in most communities necessitating unprecedented changes in the roles of individuals and families in society (Ferreira 2004, Nhongo 2004, Smit 2007, Kimokoti and Hamer 2008, UNAIDS 2008b, Lombard and Kruger 2009, Kautz et al 2010, Ogunmefun et al 2010, Pellizzoli 2011. Over the generations, the traditional strength and resilience of the African extended family represented what is commonly known as an impregnable 'safety net' capable of mitigating any crisis through interwoven ties and social networks that preserved family, kinship, and society (Foster 2000, Foster and Williamson 2000, Nhongo 2004, Moore and Henry 2005, Smit 2007.…”
Section: Resultsmentioning
confidence: 99%
“…Research on older people in Africa is scarce and the few studies done cover only a few countries without taking into consideration the wide diversity of communities on the continent of Africa or use smaller samples which make it difficult to generalize findings (Bock and Johnson 2008, Ice et al 2008, Makoni 2008, Kiggundu and Oldewage-Theron 2009, Kyobutungi et al 2009, Lombard and Kruger 2009, Muga and Onyango-Ouma 2009). …”
Section: International Journal Of Health Promotion and Education 251mentioning
confidence: 99%
See 1 more Smart Citation
“…Poor health is a major problem facing older people in South Africa, with lack of access to health facilities, overcrowding at hospitals, and lack of medication being key difficulties they encounter when seeking health services (Lombard & Kruger, 2009). Advancing the health of older persons within the framework of a transforming healthcare system and primary healthcare requires reorienting healthcare services towards health promotion, disease prevention, and equitable access to quality primary healthcare and long-term care.…”
mentioning
confidence: 99%